Scarcity amidst abundance? Reassessing the potential for cropland expansion in Africa - Chamberlin, Jordan; Jayne, Thomas S.; Headey, Derek D. (Elsevier, 2014)
Sub-Saharan Africa is typically regarded as land abundant, and previous efforts to estimate the true extent of potentially available cropland (PAC) have largely affirmed this perception. Such efforts, however, have largely focused on production potential and have underemphasized economic profitability and other constraints to expansion. This paper re-estimates PAC for Africa in a more explicit economic framework that emphasizes the returns to agricultural production under a variety of assumptions, using recent geospatial data. Existing PAC estimates for Africa are shown to be highly sensitive to assumptions about land productivity and market access, and are moderately influenced by the use of alternative data sources. The region's underutilized land resources are concentrated in relatively few countries, many of which are fragile states. Between one-half and two-thirds of the region's surplus land is currently under forest cover; conversion of forests to cropland would entail major environmental costs. Most of the continent's unexploited land resources are located far from input and output markets, limiting their economic attractiveness. In the long run, improvements in infrastructure and agricultural productivity and the growth of hinterland towns will enhance the economic returns to cropland expansion. In the short to medium term, however, the potential for profitable smallholder-based cropland expansion in most African countries is likely to be much more limited than it is typically perceived to be.